(untitled) (Research, Society and Development, 2019)
This study aimed to describe the knowledge of nurses of an Intensive Care Unit (ICU) of a mid-size Taquari Valley Hospital about Healthcare-Related Infections (IRAS). This is an exploratory, descriptive, cross-sectional study with a qualitative approach, conducted with six intensive care nurses. Data collection was performed through a semi-structured interview with guiding questions elaborated by the researcher. The interviews had their audios recorded and analyzed according to Bardin’s Content Analysis. The study showed clear understanding of nurses about the term IRAS. Respondents cited hand hygiene, use of Personal Protective Equipment (PPE), and continuing health education as tools to combat HAI. In general, they stated that HAI impact patients, increasing their length of stay, increasing costs for the institution, the presence of bacterial resistance due to the irrational use of antibiotics (ATBs). Thus, the reflection by prescribing professionals about the importance of rational use of ATBs is fundamental. Healthcare professionals involved in patient care should reflect on the impact that HAI has on the patient, improving care delivery.